Meta Analysis: Relationships of Risk Factors of Physical Activity and Obesity with Premenstrual Syndrome - Husna, Erza; Murti, Bhisma; Adriani, Rita Benya (Masters Program in Public Health, Sebelas Maret University, 2022)
Background: Premenstrual syndrome is actually experienced by almost all women wherever they are, but most teenagers think the symptoms they feel do not require further intervention or treatment. This study aims to analyze the relationship between physical activity and obesity with premenstrual syndrome based on the results of several previous similar primary studies.Subjects and Method: This study was conducted using a meta-analysis study with PICO as follows: P= women aged 17-50 years, I= high physical activity and obesity, C= low physical activity and not obesity, O= premenstrual syndrome. Article searches were conducted using electronic databases, namely Pubmed, Google Scholar, Springer Link, Clinical Key, and Proquest. Article searches were conducted using keywords and the Mesh method as follows